The Prevalence and Risk Factors of GERD among Indonesian Medical Doctors - Syam, Ari F; Hapsari, Puspita FC; Makmun, Dadang (Makara Journal of Health Research, 2016)
Background: Based on our knowledge, the study of gastrointestinal reflux disease (GERD) among certain profession has never been conducted. The aim of this study is to determine the prevalence and risk factors of GERD among Indonesian doctors. Methods: A consecutive study involving 515 doctors was conducted in October 2015. The GerdQ score was used to the diagnosis of GERD and determined its impact on daily life. All possible risk factors were also analysed. Results: A total of 515 subjects completed the questionnaire. The mean age of them was 41.37 ± 11.92 years old. Fifty-five percent of them were male and 60.6% general practitioners. The prevalence of GERD was 27.4% of which 21.0% was had GERD with low impact on daily life, and 6.4% was GERD with high impact on daily life. The statistically significant risk factors of GERD was found in age > 50 y.o (p = 0.002; OR = 2.054), BMI > 30 kg/m2 (p = 0.016; OR = 2.53), and smokers (p = 0.031; OR = 1.982). Sex and education level were not found significant statistically as the risk factors of GERD. Conclusions: The prevalence of GERD among Indonesian physician was 27.4%. We found that age over 50 y.o, obesity and smoking habit were the risk factors of GERD in Indonesian doctors.